Characterizing the Role of Protein Arginine Methyltransferase 7 (PRMT7) in Breast Cancer - Haghandish, Nasim (Université d'Ottawa / University of Ottawa, 2019)
The development of more efficient therapeutic strategies in the treatment of breast cancer relies on understanding the biological events that promote its progression. Protein arginine methyltransferases (PRMTs) are enzymes that catalyze the methylation of arginine residues within proteins resulting in changes in several biological processes. PRMTs have been shown to be aberrantly expressed in many cancers and promote tumourigenesis and cancer progression. Specifically, PRMT7 mRNA expression correlates with breast cancer aggressiveness and invasiveness. Thus, we sought to determine whether PRMT7 promotes breast cancer progression/tumourigenesis and to further identify the functional mechanisms through which this is possible. We have shown that PRMT7 is upregulated in both breast cancer tissues and cell lines. Moreover, we have shown both in vitro and in vivo that PRMT7 enhances breast cancer cell invasion and metastasis. Using biochemical experimentation, we demonstrated that PRMT7 induces the expression of matrix metalloproteinase 9 to promote invasion and subsequent metastasis. Furthermore, using proteomic experiments, we discovered many novel PRMT7-interacting proteins. Further biochemical experimentation identified eukaryotic translation initiation factor eIF2α as an interacting protein and substrate of PRMT7. We demonstrated a regulatory interplay between eIF2α methylation and phosphorylation upon cellular stress: methylation is required for S51 phosphorylation. Accordingly, we have shown that stress granule formation, in the face of cellular stresses, was significantly diminished in PRMT7-knockdown cells. We additionally found that PRMT7 plays a regulatory role in protein translation. Overall, these findings suggest that PRMT7 plays a critical role in promoting breast cancer cell invasion, metastasis, stress regulation, and protein translation.
Keywords: PRMT7; Invasion; Breast Cancer; Metastasis; Translation; Stress Granules; eIF2α